A near-infrared GPX4 fluorescent probe for non-small cell lung cancer imaging. Issue 3 (12th December 2022) - Hu, Qiao; Zhu, Wanjie; Du, Jianjun; Long, Saran; Sun, Wen; Fan, Jiangli; Peng, Xiaojun
Abstract : A near-infrared fluorescent probe ENBO-ML210 was developed. In vitro and in vivo imaging results showed that it could target and visualize GPX4 in H1299 cells, exhibiting the potential for diagnosis of non-small lung cancer. Abstract : Glutathione peroxidase 4 (GPX4) is overexpressed in non-small cell lung cancer (H1299) cells. In this work, a near-infrared fluorescent probe ENBO-ML210 was developed. In vitro and in vivo imaging results showed that ENBO-ML210 could target and visualize GPX4 in H1299 cells, exhibiting potential for the diagnosis of non-small lung cancer.